Correlation of intracranial and extracranial carotid atherosclerotic plaque characteristics with ischemic stroke recurrence: a high-resolution vessel wall imaging study - Shao, Shengyu; Wang, Tianle; Zhu, Li; Gao, Yin; Fan, Xian; Lu, Yu; Qian, Chengqun; Zhang, Manyu; Qian, Jinhua (Frontiers in Neurology, 2025)
ObjectivesTo evaluate the ability of the plaque characteristics of extracranial carotid and intracranial arteries to predict large atherosclerotic ischemic stroke recurrence via head and neck combined high-resolution vessel wall imaging (HR-VWI).MethodsThis prospective cohort study included 169 patients with large atherosclerotic ischemic stroke who underwent head and neck combined HR-VWI from April 2022 to May 2023. The baseline clinical data and atherosclerotic plaque characteristics of the intracranial and extracranial carotid arteries were collected, and the patients were followed up for 1 year, with the endpoint event defined as recurrent ischemic stroke. Clinical and imaging data were compared between the recurrent and nonrecurrent groups. Independent risk factors associated with stroke recurrence were assessed via multivariate Cox regression analysis. The receiver operating characteristic (ROC) curves of the relevant variables were also plotted, and the area under the curve (AUC) was calculated to assess their ability to predict stroke recurrence. Kaplan–Meier survival curves were used to compare the probability of stroke recurrence.ResultsDuring the 12-month follow-up, stroke recurrence occurred in 35 of the 169 patients. Multivariate Cox regression analysis revealed that the total number of intracranial and extracranial carotid plaques (p = 0.010) and coexisting extracranial carotid plaques and intracranial significantly enhanced plaques (p = 0.047) were independent risk factors for recurrent ischemic stroke. The AUCs for predicting stroke recurrence were 0.787 and 0.710, respectively. The Kaplan–Meier survival curve revealed that the risk of stroke recurrence was significantly greater in patients whose total number of intracranial and extracranial carotid plaques was >4.5 than in patients whose total number of plaques was <4.5 (p < 0.001) and was significantly greater in patients with coexisting extracranial carotid plaques and intracranial significantly enhanced plaques than in patients without coexisting plaques (p < 0.001).ConclusionA greater total number of intracranial and extracranial carotid plaques and the coexistence of extracranial carotid plaques and intracranially significantly enhanced plaques are independent risk factors associated with recurrent ischemic stroke. Head and neck combined HR-VWI may provide new indicators for the prediction of stroke recurrence, thus helping clinicians identify high-risk patients and target therapy to reduce the recurrence of ischemic events.